Impact of Financial Leverage on Firm Performance: Textile Composite Companies of Pakistan - Umer Iqbal; Muhammad Usman (SEISENSE (PRIVATE) LIMITED, 2018)
The aim of this research is to identify the relationship between financial leverage and the performance of Textile Composite Companies of Pakistan. Pakistan Textile Composite Companies which are listed in PSX (100-index) are selected.5-year data is collected from 2011-2015 and top 16 companies are selected as a sample. Using descriptive statistics, correlation analysis, and a regression model to identify the results. Results show that financial leverage has a negative and significant effect on firm ROE and financial leverage has a positive and significant effect on firm ROA. Further study indicates that the high-interest rate and more amount of debt decrease the value of equity and has a negative impact on firm performance. On the other hand, the amount of debt has a positive impact on firm ROA. Results show that financial leverage has a positive impact on firm performance if the amount of debts do not exceed the amount of equity.